NONANTIBIOTICS ENHANCE THE ANTIBACTERIAL ACTIVITY OF CEFTRIAXONE AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS - Krishnan, Akilandeswari; Kandasamy, Ruckmani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Antibiotic resistance is one of the most persistent issues worldwide nowadays, and methicillin-resistant Staphylococcus aureus (MRSA) infection is one such issue where the standard therapeutic procedures involving powerful antibiotics have failed in controlling the infection. Methods: In the present study, the antibacterial potency of the nonantibiotics troxipide (TR), mebeverine hydrochloride (Hcl), and their combinations with ceftriaxone (CEF) against MRSA has been investigated using microbiological assays of microplate dilution method and combination index interpretations of the nonantibiotics with β-lactam antibiotic CEF and the zone of inhibition method. Results: The nonantibiotics ME and TR inhibited resistant strain tested in vitro in the checkerboard assay, where the results showed that CEF and TR exhibited minimum inhibitory concentration (MIC) at concentrations of 50 μg/ml and 318 μg/ml, respectively. Interestingly, CEF when combined with TR reduced the MIC to 8 μg/ml and 78 μg/ml. According to the results, CEF with TR exhibited synergistic interactions at the fractional inhibitory concentration of 0.36–1.4. ME and TR and its combinations, CEF with ME, and CEF with TR have considerable anti-MRSA efficacy, with synergism though at 36 h of incubation. Conclusion: ME and TR being antispasmodic and antiulcer drugs can also be used against MRSA infections, which could prove to be favorable in the reduction of dosage of antibiotics such as CEF, and cutting down the need for additional administration of antibiotics to the patients affected with multiple complications such as gastrointestinal ulcer, spasm difficulties, and infection.